Strategies to prevent workplace sexual harassment among Iranian nurses: A qualitative study - Zeighami, Maryam; Zakeri, Mohammad Ali; Mangolian Shahrbabaki, Parvin; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
Background Sexual harassment in the workplace has many negative consequences for nurses and the delivery of patient care. Appropriate policies and strategies can help to create a safe work environment for nurses. Therefore, the present study aimed to investigate Iranian nurses’ strategies for preventing sexual harassment in the workplace. Materials and methods This qualitative descriptive-explorative study used conventional content analysis to investigate how Iranian nurses cope with sexual harassment (n = 22). Participants were selected using a purposeful sampling method. Data was collected through in-depth, semi-structured interviews from September 2020 to April 2021. In order to obtain rich information, maximum variation was considered (age, sex, work experience, level of education, marital status, and type of hospital and ward). The Guba and Lincoln criteria were used to increase the study’s trustworthiness, while the Graneheim and Lundman approach was used to analyze the content. Results One hundred and twelve codes, one main category, four categories, and 12 subcategories were extracted. The main category, strategies to prevent sexual harassment among nurses in the workplace, includes four categories: behavioral response, working conditions adjustment, informing, and performance of hospital security guards. The most common strategy used by nurses was behavioral response. Conclusion Basic measures are required to prevent sexual misconduct against nurses, which is an obvious part of the professional organizational culture. Managers and policymakers should develop workplace ethics, legal accountability, and safety. They should also develop training programs and prevention strategies to help nurses improve their coping skills. Further quantitative and qualitative research in other healthcare groups is required to confirm the findings of this study.